A Comparative Study on the Efficacy of Platelet-Rich Fibrin vs. Standard Care in Reducing Pain and Swelling Post-Surgical Extraction of Impacted Mandibular Third Molars - pervez, Jazib; Manzoor, Sobia; Hassan, Taimur ul; Langrial, Rizwan Zafar; Ahmed, Mujeeb; Ali, Memoona (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare outcomes of Application of platelet-rich fibrin versus standard care on pain and swelling in patients who are having surgical extraction of impacted mandibular 3rd molars.Study Design: Randomized controlled trial (ACTRN: 0000387594).Place and Duration of Study: Bakhtawar Amin Dental College & Hospital, Multan Pakistan, from Aug 2022 to Feb 2023.Methodology: One hundred and sixty-eight patients included for surgical extraction of impacted third molar, were randomly assigned to Group A (platelet-rich fibrin) and Group B (standard care). In Group A, PRF was introduced in extraction sockets. On follow-up the outcomes in the form of pain and facial swelling were assessed on 3rd post-operative day.Results: Mean age of patients in Group A was 34.45±9.04 years and Group B was 36.30±9.12 years with p-value of 0.187. There were 31(36.9%) males and 53(63.1%) females in Group A and 28(33.3%) males and 56(66.7%) females in Group B with insignificant p-value of 0.628. Mean facial swelling in Group A was 9.75±1.33mm and Group B was 11.19±1.48mm with                     p-value of